Sterilization and Contraception Costs: An Educational Needs Assessment and Intervention. (October 2016) - Martinez, Anjali; Weeks, Corinne; Keller, Jennifer
Abstract : BACKGROUND: Understanding the costs associated with healthcare is an essential component of being an effective physician and has been recognized as one of the five essential competencies of systems-based practice. Despite this level of importance, there is little published about assessing knowledge associated with sterilization costs or strategies to educate trainees about cost. This project was designed to perform a needs assessment, create a curriculum to teach residents about costs of sterilization, and to determine the impact of the educational intervention. METHODS: Obstetrics and Gynecology residents and faculty were surveyed regarding their baseline knowledge and attitudes of the cost of sterilization and long-term contraceptive options. An interactive curriculum was designed for the residents around cognitive gaps, and the residents were resurveyed after the educational session. RESULTS: Twelve residents including PGY-2 (n=3), PGY-3 (n=4) and PGY-4 (n=5) and 15 faculty members participated in the study. Residents considered it important to understand the cost of comparable sterilization options (mean: 4.14; scale: 1–5) but did not feel knowledgeable about these costs (mean: 1.83; scale 1–5). Faculty also felt this topic was important (mean: 4.3; scale 1–5) but felt more knowledgeable (mean: 3.0; scale 1–5). After implementation of the curriculum, residents felt significantly more knowledgeable (mean: 3.25 versus 1.83, P <.01). DISCUSSION: Residents recognize the knowledge deficit associated with sterilization costs and consider understanding costs to be important. Using an educational intervention, we demonstrate improved knowledge about costs and plan to reassess in 6 months to determine retention.